Secondary organic aerosol formation from semi‐ and intermediate‐volatility organic compounds and glyoxal: Relevance of O/C as a tracer for aqueous multiphase chemistry. Issue 5 (7th March 2013) - Waxman, Eleanor M.; Dzepina, Katja; Ervens, Barbara; Lee‐Taylor, Julia; Aumont, Bernard; Jimenez, Jose L.; Madronich, Sasha; Volkamer, Rainer
Abstract [1] The role of aqueous multiphase chemistry in the formation of secondary organic aerosol (SOA) remains difficult to quantify. We investigate it here by testing the rapid formation of moderate oxygen‐to‐carbon (O/C) SOA during a case study in Mexico City. A novel laboratory‐based glyoxal‐SOA mechanism is applied to the field data, and explains why less gas‐phase glyoxal mass is observed than predicted. Furthermore, we compare an explicit gas‐phase chemical mechanism for SOA formation from semi‐ and intermediate‐volatility organic compounds (S/IVOCs) with empirical parameterizations of S/IVOC aging. The mechanism representing our current understanding of chemical kinetics of S/IVOC oxidation combined with traditional SOA sources and mixing of background SOA underestimates the observed O/C by a factor of two at noon. Inclusion of glyoxal‐SOA with O/C of 1.5 brings O/C predictions within measurement uncertainty, suggesting that field observations can be reconciled on reasonable time scales using laboratory‐based empirical relationships for aqueous chemistry.